REVIEW OF CMOS-BASED TEMPERATURE SENSORS - MARTYNIUK, VOLODYMYR; MALIUK, OLEKSANDR (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article provides an extensive exploration of the current landscape of CMOS temperature sensor technology, providing insights into various groundbreaking advancements. One notable innovation discussed is the integration of a phase-locked loop (PLL) architecture into temperature sensors, enabling the seamless transmission of temperature data to digital outputs within the frequency domain without the reliance on an external reference source. Furthermore, the article delves into the emergence of energy-efficient temperature sensors and CMOS-based temperature sensors that exploit the thermal dependencies of current flow, specifically optimized for application on a 65 nm scale. In addition to highlighting these technological advancements, the article conducts in-depth discussions on the technical characteristics, operational methodologies, and potential future developments of CMOS temperature sensors. The diverse range of applications across various industries, including but not limited to medical, automotive, and industrial automation sectors, is thoroughly explored, emphasizing the versatility and wide-ranging impact of these sensors. Furthermore, the article provides detailed analyses of the architectural designs, electrical schematic diagrams, and graphical research results associated with CMOS temperature sensors, offering valuable insights into their underlying mechanisms and performance metrics. A significant emphasis is placed on the significance of CMOS (Complementary Metal-Oxide-Semiconductor) technology as a key enabler of these sensor innovations. Recognized for its inherent advantages such as miniaturization, high integration capability, and cost-effectiveness, CMOS technology stands out as a frontrunner in driving the realization of advanced sensor technologies across various domains. By offering a comprehensive exploration of these cutting-edge advancements, the article aims to contribute to the ongoing discourse surrounding CMOS temperature sensors and their transformative potential. It seeks to inform and inspire researchers, engineers, and industry professionals alike to further explore and harness the capabilities of CMOS technology for the advancement of temperature sensing solutions, thereby fostering innovation and progress in the field.